Sharing the costs of complex water projects: Application to the West Delta water conservation and irrigation rehabilitation project, Egypt - Stefano Moretti; Fioravante Patrone; Ariel Dinar; Safwat Abdel-Dayem (Games, 2016)
Effective sharing mechanisms of joint costs among beneficiaries of a project are a fundamental requirement for the sustainability of the project. Projects that are heterogeneous both in terms of the landscape of the area under development or the participants (users) lead to a more complicated set of allocation mechanisms than homogeneous projects. The analysis presented in this paper uses cooperative game theory to develop schemes for sharing costs and revenues from a project involving various beneficiaries in an equitable and fair way. The proposed approach is applied to theWest Delta irrigation project. It sketches a differential two-part tariff that reproduces the allocation of total project costs using the Shapley Value, a well-known cooperative game allocation solution. The proposed differential tariff, applied to each land section in the project reflecting their landscape-related costs, contrasts the unified tariff that was proposed using the traditional methods in the project planning documents.
Keywords: Q15; Q58; H43; 330; water project; cost allocation; cooperative game; Shapley Value; sustainability; stability; Egypt; West Delta